Importance of ultradian oscillations in neurogenesis during development and its implications for spinal cord regeneration - Leino, Sami A.; Soto, Ximena (Frontiers in Cell and Developmental Biology, 2025)
The formation of a functional nervous system during development and its maintenance in adulthood rely on precise regulation of neural stem cell (NSC) proliferation and differentiation. During neurogenesis, progenitor cells use various cellular and molecular mechanisms to balance these processes. Among these, dynamic signal encoding, specifically ultradian oscillations, which are regular protein fluctuations occurring over a few hours, has emerged as a key mechanism underlying NSC fate decisions. In adults, reactivation of quiescent NSCs, proliferation, and differentiation are also controlled by ultradian oscillations. Furthermore, these ultradian dynamics signals are modulated by microRNAs and are considered critical for the ability of neural progenitors to transition between different states. Altogether, these findings may have potential significance for our understanding of NSC reactivation and differentiation in the context of injury or neurodegeneration. The mammalian spinal cord harbours endogenous multipotent NSCs that respond to injury but mostly generate astrocytes and do not undergo neurogenesis. By contrast, many anamniotes regenerate spinal cord neurons from endogenous progenitors, despite the same molecular signalling pathways being activated, suggesting that subtle differences in how these pathways are regulated may result in different regenerative outcomes. Whether oscillatory dynamics could influence the reactivation and differentiation of NSCs upon spinal cord injury remains to be determined. This review explores the role of transcription factor ultradian oscillations in neurogenesis and how microRNAs modulate them. Additionally, we examine evidence for the role of ultradian dynamics in the reactivation of quiescent NSCs and their potential significance for regenerative neurogenesis in the context of spinal cord injury.